Serum Copper levels in adolescents 17-19 years old based on stunted and obese status - Nadhea Alriessyanne Hindarta; M Sulchan; Hartanti Sandi; Nuryanto Nuryanto (Alma Ata University Press, 2023)
ABSTRAKLatar Belakang: Individu dengan status gizi stunted memiliki risiko mengalami obesitas saat remaja atau dewasa. Status stunted dan obesitas sering dikaitkan dengan kejadian inflamasi dan potensi stress oksidatif yang dapat ditandai dengan peningkatan kadar serum tembaga. Tujuan: Penelitian ini bertujuan untuk menganalisis kadar serum tembaga pada remaja usia 17-19 tahun berdasarkan status stunted dan obesitas. Metode: Penelitian ini menggunakan rancangan cross sectional. Sebanyak 91 subjek dipilih secara random sampling berdasarkan kriteria inklusi dan eksklusi. Status obesitas diukur menggunakan lingkar pinggang per tinggi (WHtR) dan status stunted diukur menggunakan tinggi badan per umur (TB/U). Pengukuran kadar serum tembaga dianalisis menggunakan teknik ICP-OES dengan nilai normal serum tembaga sebesar 0.7-1.4 mg/L. Analisis data meggunakan uji Anova, uji korelasi Pearson, dan uji T Independen. Hasil: Rerata kadar serum tembaga pada kelompok stunted-obesitas sebesar 0,83±0,21, stunted 1,11±0,28, obesitas 0,72±0,17, dan normal 0,60±0,37. Terdapat perbedaan bermakna kadar serum tembaga kelompok stunted dengan kelompok lain. Kadar serum tembaga memiliki korelasi negatif dengan TB/U (r=-0,337, p=0,001). Kesimpulan: Status stunted, obesitas, dan stunted-obesitas meningkatkan kadar serum tembaga meskipun masih dalam kategori normal. Ada perbedaan bermakna kadar serum tembaga berdasarkan status stunted dan obesitas, serta adanya korelasi negatif kadar serum tembaga dengan TB/U. KATA KUNCI: obesitas; remaja; serum tembaga; stunted, stunted-obesitas ABSTRACTBackground: Stunted have a risk of obesity in the adolescent or adult period. Stunted and obese status were associated with inflammation and oxidative stress that marked by increased serum copper levels.Objectives: This study was to describe difference of serum copper levels in adolescents 17-19 years old based on stunted and obese status.Methods: This study was using cross sectional design. There were 91 adolescents as the sample of this study and selected by random sampling based on inclusion and exclusion criterias. The obese status was measured by waist to height ratio (WHtR) and stunted status was measured by height age of z-score (HAZ). The serum copper levels were analyzed by ICP-OES with normal copper serum value of 0.7-1.4 mg/L. The data were analyzed by Anova test, Pearson correlation, and Independent t-test.Results: The mean value of serum copper level in stunted-obese group were 0.83 ± 0.21, stunted group were 1.11 ± 0.28, obese group were 0.72 ± 0.17, and normal group were 0.60 ± 0.37. There was a significant difference of serum copper level between the stunted with other groups. There was a negative correlation between serum copper level and HAZ (r = -0.337, p = 0.001).Conclusions: Stunted, obese, and stunted-obese status were able to increase serum copper level but still in normal range. A significant difference was found in serum copper levels based on stunted and obesity status, as well as a negative correlation between serum copper level and HAZ.KEYWORD: adolescents; obese status; stunted status, stunted-obese, serum copper levels